Schistosome-induced cholangiocyte proliferation and osteopontin secretion correlate with fibrosis and portal hypertension in human and murine schistosomiasis mansoni - Pereira, Thiago A. (Clin Sci (Lond), 2015)
Schistosomiasis is a major cause of portal hypertension worldwide. It associates with portal fibrosis that develops during chronic infection. The mechanisms by which the pathogen evokes these host responses remain unclear. We evaluated the hypothesis that schistosome eggs release factors that directly stimulate liver cells to produce osteopontin (OPN), a pro-fibrogenic protein that stimulates hepatic stellate cells to become myofibroblasts. We also investigated the utility of OPN as a biomarker of fibrosis and/or severity of portal hypertension. Cultured cholangiocytes, Kupffer cells and hepatic stellate cells were treated with soluble egg antigen (SEA); OPN production was quantified by quantitative reverse transcriptase polymerase chain reaction (qRTPCR) and ELISA; cell proliferation was assessed by BrdU (5-bromo-2'-deoxyuridine). Mice were infected with Schistosoma mansoni for 6 or 16 weeks to cause early or advanced fibrosis. Liver OPN was evaluated by qRTPCR and immunohistochemistry (IHC) and correlated with liver fibrosis and serum OPN. Livers from patients with schistosomiasis mansoni (early fibrosis n=15; advanced fibrosis n=72) or healthy adults (n=22) were immunostained for OPN and fibrosis markers. Results were correlated with plasma OPN levels and splenic vein pressures. SEA-induced cholangiocyte proliferation and OPN secretion (P<0.001 compared with controls). Cholangiocytes were OPN (+) in Schistosoma-infected mice and humans. Liver and serum OPN levels correlated with fibrosis stage (mice: r=0.861; human r=0.672, P=0.0001) and myofibroblast accumulation (mice: r=0.800; human: r=0.761, P=0.0001). Numbers of OPN (+) bile ductules strongly correlated with splenic vein pressure (r=0.778; P=0.001). S. mansoni egg antigens stimulate cholangiocyte proliferation and OPN secretion. OPN levels in liver and blood correlate with fibrosis stage and portal hypertension severity.